Clinical and Radiologic Characterization of Frontal Sinusitis in the Pediatric Population. (August 2021) - Velasquez, Nathalia; Strober, William; Shaffer, Amber; Stapleton, Amanda
Introduction: Frontal sinusitis in the pediatric population is a disease that has not been thoroughly studied or characterized. The goals of this study are to characterize the clinical presentation, radiologic variables, treatment modalities, complications, and prognosis associated with acute and chronic frontal sinus disease in the pediatric population. Methods: IRB-approved retrospective cohort study of pediatric patients who were diagnosed with acute (AFS) or chronic frontal sinusitis (CFS) and underwent frontal sinus surgery at a tertiary level Children's Hospital from 2006 to 2016. Patients with AFS were compared to patients with CFS. Statistical analysis completed using chi-square test or Fisher's exact test, statistical significance set at P  < .05. Results: A total of 19 patients with AFS and 15 patients with CFS were analyzed. There was a male predominance in AFS and female predominance in CFS ( P  < .05).AFS patients were less likely to have allergies, prior sinus disease, or significant comorbidities ( P  < .05).Additionally, AFS patients presented with constitutional, neurologic, and ocular symptoms. The CFS group had predominantly sinonasal symptoms. CT-scan analysis showed that AFS patients had higher prevalence of complex frontal anatomy (Type-II cells, concha bullosa) compared with CFS patients ( P  < .05). Culture results were positive in 78% of the AFS group, with S. Anginosus (53%), Anaerobes (20%), and normal flora (17%). In the CFS group cultures were positive in 60% of the patients, 56% grew normal flora, 13% H. Influenzae, 6.5% Pseudomonas, and 24.5% other species. CFS patients were more likely to have persistent sinus disease and require repeat sinus procedures ( P  < .05). Conclusion: There are 2 distinct presentations of frontal sinus disease in the pediatric population. Patients with AFS vary significantly from those with CFS. Males, ages 13 to 18 years old, who cultured positive for S. Anginosus (former S.Milleri ) dominated the AFS subgroup. Whereas as female patients with a history of allergic rhinitis and muco-cilliary disease were more prominent in the CRS subgroup. Correct identification and understanding of these 2 different entities are crucial for the appropriate short and long-term patient management.